TINDAK TUTUR PENJUAL DAN PEMBELI DI PASAR KEMUNING KOTA PONTIANAK - Mathilda Mathilda; Ahmad Rabi ul Muzammil; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe method that is used in this research is descriptive method with qualitative research. The data source used in this research is oral language which is spoken by the buyer and the seller using BMDP. The data in this research is in the form of speech, words, and dialogue which contain speech acts between the buyer and the seller. The technique of data collection which is used in this research is observation, see, and tap. The instrument that the writer uses in this research is the researcher, a camera, and stationaries. The data analysis of this research includes four steps which are transcription, translation, clarification, and analysis. The locutionary speech act whis is found in this research is assertive, directive, commisive, expressive, and declarative. The speech act which contain in this research in Pontianak Kemuning Market is the buyer and the seller as speakers and speech partners, the purpose is to tell, to ask, and to complain in a relaxed tone and speak directly in informal conditions. The function of speech act which is used in this research is competitive, fun, collaborating, and conflicting. This research provides three texts of negotiation and RPP Model curriculum 2013 class X Even semester. Keywords: Market, Pontianak Malay Language, Speech Act